Investigation on structural and H2 gas sensing response of AlCdZnNiFe2O4 sensor material. Issue 1 (1st January 2022) - Sankaranarayanan, R.; Shailajha, S.; Dineshkumar, C.; Felchiya jasmine, A.
Abstract: Synthesis of mixed spinel ferrite nanocomposites Alz Cdy Znx @Ni1-x-y-z Fe2 O4 through sol-gel method provides an excellent opportunity to develop a new generation of gas sensors. The single-phase cubic structure was confirmed and the crystallite size increases with increasing the substitution ratios due to the successful integration of the cations into the cubic system without changing the original structure. FTIR analysis was used to identify the stretching bending vibration of NiFe2 O4 and its functional groups. The replacement of Ni 2+ ions by Zn 2+, Cd 2+, and Al 3+ ions play a major role in the occupation of Ni 2+ and Fe 3+ ions between octahedral B and tetrahedral A sites and it leads to enhance response and recovery times. The FESEM images show an increase in the particle size with polyhedral shape of nanocomposites in the range of 135–342 nm and it is strongly affecting the sensibility of the sensor materials. The nanoparticles were pressed into cylindrical pellets to measure the H2 gas detection of the novel sensor material. The hydrogen (H2 ) gas sensing behavior of sensor material (x + y + z = 0.45) shows the remarkable response times such as 35, 76, and 20 s to the lower concentrations 25, 50, and 100 ppm, respectively at 250 °C. Graphical abstract: Image 1